Type C/D botulism in the waterfowl in an urban park in Italy. (December 2018) - Badagliacca, Pietro; Pomilio, Francesco; Auricchio, Bruna; Sperandii, Anna Franca; Di Provvido, Andrea; Di Ventura, Mauro; Migliorati, Giacomo; Caudullo, Mario; Morelli, Daniela; Anniballi, Fabrizio
Abstract: This report describes an outbreak of botulism occurred among a free-living population of mallards ( Anas platyrhynchos ) and geese ( Anser anser ) in an urban park. Mortality rate among investigated population was 86, 8% (118 dead out of 136). Twenty-seven carcasses were collected for macroscopic examination and screened for microbiological, virological, toxicological investigations. A sick mallard was captured and neurological symptoms were observed. No causative agent of viral avian diseases was found in the examined animals and screening for environmental neurotoxic substances proved negative as well. In contrast, microbiological cultures from specimens tested positive for botulinum toxin-producing clostridia. Blood serum and fecal extract of the sick mallard proved positive for botulinum neurotoxin in the standard mouse protection test using reference Clostridium botulinum type C antitoxin. Gene content of cultured strains showed a mosaic composition of bont /C and bont /D sequences, defining them as type C/D chimeric organisms. Highlights: We investigated a rare occurrence of botulism in the waterfowl in an urban park. We documented clinical signs consistent with the limberneck syndrome in a mallard. Death dating of carcasses defined the botulism as slowly spreading disease. Reported data confirmed the presence of type C/D botulism in the waterfowl in Italy.